Cutaneous blood flow in the forearm of highly trained windsurfers - Heylen, E.; Simon, B.; Guerrero, F.; Elkaim, J.-P.; Salag, B.; Mansourati, J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Objective: We undertook this study to determine whether long-term high intensity exercise involving the forearm musculature would modify cutaneous endothelial vasoreaction. Methods: We compared a group of 9 highly trained windsurfers (mean age : 24.5 ± 1.6 years) to a control group of 8 sedentary individuals (22.9 ± 0.4 years, NS). Laser Doppler was used to measure cutaneous blood flow in the resting state (baseline), during post-occlusive hyperaemia (endothelium-dependent vasodilation) and local heating to 42°C (maximal vasodilation). Results: Lipid profile was similar in both groups. Resting heart rate was significantly lower in windsurfers. Baseline values were similar in both groups. During reactive hyperaemia, peak value (RH) was significantly higher in the windsurfers group. Peak value in response to local heating 42°C (T peak) was higher in the windsurfers group but that was not statistically significant (see Table). Conclusion: Endothelial function of cutaneous microcirculation is significantly improved in the forearm of highly trained windsurfers when compared to sedentary controls.